2010
DOI: 10.1111/j.1365-2982.2010.01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Can eating disorders cause functional gastrointestinal disorders?

Abstract: Functional gastrointestinal disorders (FGIDs) are very common (up to 98%) in patients with an eating disorder (ED). Boyd et al. discuss in this issue of Neurogastroenterology & Motility that FGIDs can persist independently on the outcome of the ED. Their findings leave room for speculation on the mechanisms underlying FGIDs in patients with an ED. FGIDs result from a complex interaction of biological, psychosocial and social factors. The altered eating behavior seen in EDs is strongly associated with disturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
(50 reference statements)
1
15
0
5
Order By: Relevance
“…These GI problems can complicate the treatment of ED and the GI symptoms shift during the course of recovery. Some remain, others disappear, and others develop (11,(13)(14)(15). An important underlying mechanism for these observations is the microbiota-gut-brain-axis which allows bidirectional communication between the central nervous system and the gut (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These GI problems can complicate the treatment of ED and the GI symptoms shift during the course of recovery. Some remain, others disappear, and others develop (11,(13)(14)(15). An important underlying mechanism for these observations is the microbiota-gut-brain-axis which allows bidirectional communication between the central nervous system and the gut (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…An important underlying mechanism for these observations is the microbiota-gut-brain-axis which allows bidirectional communication between the central nervous system and the gut (16,17). Janssen (15) therefore postulated that GI physiology disturbed by an ED, in combination with other mental illnesses, could lead to the maintenance or intensification of symptoms (15).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological variables such as somatization, neuroticism, and anxiety are significant predictors of FGIDs, both type and the presence of multiple coexistent FGIDs among ED patients [18]. Janssen [19] has suggested that once FGIDs are established in ED patients, psychological and physiological factors will strengthen each other such that FGIDs and FGID symptoms could persist independent of the current status of the ED [4].…”
Section: Discussionmentioning
confidence: 98%
“…Eating salty food is not good for the health and may increase the risk of incidence of stomach cancer (Park et al, 2016). While having an unhealthy diet or overeating can induce heavy gastrointestinal burden and go against one's overall health (Janssen, 2010). Meanwhile, spending a prolonged amount of time online may cause backache, neck, finger, wrist, and arm pain, as well as emotional fluctuation, tension and anxiety, fatigue and other SHS symptoms (Karacic & Oreskovic, 2017).…”
Section: Discussionmentioning
confidence: 99%